Environmental forcing of phytoplankton in a Mediterranean estuary (Guadiana Estuary, southwestern Iberia): a decadal of anthropogenic and climatic influences - Barbosa, Ana B. (2012)
Phytoplankton seasonal and interannual variability in theGuadiana upper estuarywas analyzed during 1996–2005, a period that encompassed a climatic controlled reduction in river flow that was superimposed on the construction of a dam. Phytoplankton seasonal patterns revealed an alternation between a persistent light limitation and episodic nutrient limitation. Phytoplankton succession, with early spring diatom blooms and summer–early fall cyanobacterial blooms, was apparently driven by changes in nutrients, water temperature, and turbulence, clearly demonstrating the role of river flow and climate variability. Light intensity in the mixed layer was a prevalent driver of phytoplankton interannual variability, and the increased turbidity caused by the Alqueva dam construction was linked to pronounced decreases in chlorophyll a concentration, particularly at the start and end of the phytoplankton growing period. Decreases in annual maximum and average abundances of diatoms, green algae, and cyanobacteria were also detected. Furthermore, chlorophyll a decreases after dam filling and a decrease in turbidity may point to a shift from light limitation towards a more nutrient-limited mode in the near future.